Storia, identità e canoni letterari - Ayse Saracgil (Strumenti per la didattica e la ricerca, 2013)
This volume collects the interventions of the post-doctoral fellows and PhD students of the University of Cluj Napoca, the University of Bucharest and the University of Florence (Mediterranean Cultures; Doctoral School of Comparative Languages, Literatures and Cultures, specialisation in Language, Literature, Philology: Intercultural Perspectives) presented in occasion of the seminar Storia, identità e canoni letterari ("History, identity and literary canons", Florence, 22-23 November 2011). The contributions are centred on the idea of canon, as a cultural construct founding modern national identities. Another trace is the literary and cultural hybridisations between different geographies. For the Romanian context, the contributions pay particular attention to the movements of the avant-garde of the early 1900s. Some contributions account for the most problematic aspects of the contemporary world using interdisciplinary approaches.